The Problems of Secularism in the Albanian School System in 1920 -1930’s - Gjini, Lorena (Richtmann Publishing, 2012)
After the First World War, the internal situation in Albania was very heavy. Education in Albania developed under theinfluence Italians, Austro – Hungarians and French in areas where they had control during war. By creating Lushnjagovernment, education problems begin to be treated with priority by the Albanian State.Thus the period from 1920 to 1935,characterized by a long struggle for unification, nationality and secularism of the school system. In this period, three pedagogicalcongresses were formed (1920, 1922, 1924) as well as an educational reform that will be entered in the history of Albanianeducation as the